Faktor Risiko yang Berhubungan dengan Perilaku Seksual Pranikah pada Remaja Akhir Usia 20-24 Tahun di Kelurahan Namosain - Defika Adriana Leonora Ello; Yuliana Radja Riwu; Honey Ivon Ndoen (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Premarital sexual behavior in adolescents is a serious problem in Indonesia. Every year the phenomenon of free sex or premarital sexual behavior by teenagers continues to increase and even adds to the rate of STI transmission and the incidence of HIV/AIDS. The purpose of this study was to determine the risk factors associated with premarital sexual behavior in late adolescents aged 20-24 years in the Namosain Village. This type of research is a quantitative study using a cross sectional research design. The sample size of this study was 340 late adolescents aged 20-24 years in the Namosain village. The results of this study showed that there was no relationship between knowledge and premarital sexual behavior with a p-value = 0.339 > α = 0.05. There is a relationship between sources of information and premarital sexual behavior with a p-value = 0.004 < α = 0.05. There is a relationship between peers and premarital sexual behavior with a p-value = 0.000 < α = 0.05. There is no relationship between parenting style and premarital sexual behavior with a p-value = 1.000 > α = 0.05. There is a relationship between dating style and premarital sexual behavior with a p-value = 0.000 < α = 0.05. Suggestions for parents can apply democratic parenting to children, so they can build good communication with children.